Analisis Net Interest Margin Dan Capital Adequacy Ratio Terhadap Kinerja Keuangan Di Bursa Efek Indonesia - Fitriyani, Eka; Wage, Sunarto (LPPM Universitas Putera Batam, 2021)
This research is shown to analyze the net interest margin and capital adequacy ratio against the financial performance of banks listed on the Indonesia Stock Exchange. The population in this study were all banks listed on the Indonesia Stock Exchange, namely 44 banks and using a sample of 28 according to the criteria set in the sample. The research instrument is documentation and uses secondary data sources obtained from banking financial reports listed on the Indonesia Stock Exchange. The data analysis technique used in this research is statistical test with classic assumption test in the form of normality test, multicollinearity test, heterocedacity test and autocorrelation test and using multiple linear regression test consisting of t test and F test, using SPSS version 25 F in this study shows that the variables net interest margin and capital adequacy ratio together have an effect on return on assets. The results of the coefficient of determination R² showed a value of 0.246 (24%). The remaining 76% was influenced by other variables that were not included in this research.